A case study on teacher portfolio with early childhood teachers. Issue 2 (4th March 2021) - Aras, Selda
ABSTRACT: Effective professional development that builds meaningfully on teachers' classroom experiences should provide teachers opportunities to reflect on their own teaching acts. Teachers who are aware of what they are doing as a teacher, act with the awareness of what they professionally need and transform their practices. A teacher portfolio is an unfolding of teachers' understandings about their development as a professional. This study aimed to explore four early childhood teachers' experiences through the teacher portfolio. Case study design was utilized with an inductive approach in order to explore this contemporary topic. Semi-structured interviews, reflective journals, focus group interviews, and teacher portfolios were used as data collection tools. This study provided evidence for the contributions of the teacher portfolio in terms of reflecting on teaching acts, needs assessment and professional development plan, and teacher portfolio as a portrayal of professional growth.